SOSIALISASI LITERASI KEUANGAN PADA SISWA/I SMK NEGERI 1 MEDAN - Aliah, Nur; Rizkina, Miftha (Jurnal Pengabdian Bukit Pengharapan, 2024)
The community service activity entitled "Socialization of Financial Literacy among Students of SMK Negeri 1 Medan" aims to increase students' and teachers' understanding of personal financial management and the application of simple accounting. The program involves a lecture, discussion and workshop-based approach, designed to build financial literacy and entrepreneurship skills. The results of the activity showed an increase in participants' understanding of financial management concepts, which was reflected in the results of the pre-test and post-test evaluations. Some students also start to apply simple bookkeeping in their small businesses. In addition, teachers receive training to integrate financial literacy in learning. Despite challenges such as limited facilities, this program has succeeded in building an important foundation for the sustainability of financial literacy education at SMK Negeri 1 Medan.